Treatment of T-AYU-HM Premium and Onion steam vaporisation on possible re-infection or reactivation Covid-19 patient: A case study (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
During the coronavirus pandemic, we are at stage where now observations are being recorded for possibilities of reinfection or reactivation in patients suffered from coronavirus. The heterogeneous natures of coronavirus infection producing complications in patients require a lot of critical care and monitoring. Post-discharge from hospitals, proper self-care and immune booster supplements have become a must. Patient's self-immunity, post-discharge medication non-adherence, casual approaches in self-care might become reasons for reinfection or reactivation of the virus in patients. Reporting case studies on reinfection or reactivation of coronavirus help enhance post-discharge management and safety guidelines. A 50-year-old male infected with coronavirus was admitted to the hospital, receiving treatment and discharge after 10 days. A 2 months later due to difficulty breathing, coughing, and fever he presented to our clinic. On examination and laboratory investigation, it was considered possible reinfection or reactivation of coronavirus in a patient. With proper discussion and prior consent we initiate treatment with T-AYU-HM premium and onion steam vaporization. During follow-up visit the observations like clinical and laboratory markers suggest remarkable improvement and alleviation of symptoms. During 2 months of treatment adherence, we also observed a marked decrease in lung opacities and no honeycombing in HRCT than in previous reports. This case report recommends the importance of an alternative medicine system restricted to the prophylactic purpose and has a role to play in post covid19 infected patients.